2018
DOI: 10.1248/bpb.b18-00084
|View full text |Cite
|
Sign up to set email alerts
|

miR-22-Notch Signaling Pathway Is Involved in the Regulation of the Apoptosis and Autophagy in Human Ovarian Cancer Cells

Abstract: microRNA-22 (miR-22) is a brain-enriched regulatory gene which has been reported to be involved in the development of cancers. The Notch signaling pathway exerts important functions in cell growth. This study is designed to investigate the mechanisms of miR-22-Notch signaling pathway in apoptosis and autophagy of human ovarian cancer cells. After over-expressing miR-22 in human ovarian cancer cell lines OVCAR-3 and SKOV3, cell viability is determined by 2,3-bis-(2-methoxy-4-nitro-5-sulfophenyl)-2H-tetrazolium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…MiR‐22 has already been found to act as either a tumor suppressor or an oncomiRNA in different cancers. Recent research found that miR‐22 promotes autophagy of human ovarian cancer cells through the suppression of the Notch signaling pathway. In contrast, we observed miR‐22 to promote osteosarcoma chemoresistance via autophagy repression and stimulation of apoptosis, suggesting that miR‐22 functions in a disease‐specific context.…”
Section: Discussioncontrasting
confidence: 60%
“…MiR‐22 has already been found to act as either a tumor suppressor or an oncomiRNA in different cancers. Recent research found that miR‐22 promotes autophagy of human ovarian cancer cells through the suppression of the Notch signaling pathway. In contrast, we observed miR‐22 to promote osteosarcoma chemoresistance via autophagy repression and stimulation of apoptosis, suggesting that miR‐22 functions in a disease‐specific context.…”
Section: Discussioncontrasting
confidence: 60%
“…10) circPTN regulates proliferation activity in glioma by targeting miR-145-5p/miR-330-5p. 30) Accumulating evidence points to the potential role of miRNAs in DKD progression. 31) It is reasonable to speculate that circACTR2 may regulate DKD by sponging miRNA or other targets, which encourages continued exploration of circACTR2 in the pathogenesis of DKD.…”
Section: Discussionmentioning
confidence: 99%
“…The miR-22, a multifunctional molecule and broadly expressed in multitype of tissues in mammals, was found involved in the pathogenesis of many diseases, such as cancer, arthritis, kidney injury, and osteogenic impairment. [15][16][17][18] However, the role of lncRNA-TM1P3/miR-22/ALK1 in cartilage remained unknown, especially their role in ECM degradation and OA pathogenesis. Therefore, the present study was aimed to investigate the interaction of miRNA-22 and lncRNA-TM1P3, which contributed to the overexpression of MMP13 in chondrocyte ECM degradation in the pathogenesis of OA.…”
Section: Introductionmentioning
confidence: 99%